What Shapes Visitor Experience at Religious Destinations? Deploying a Systematic Review to Identify Visitor Experience Constructs - Priyanka Singh; Amit Singh; Anil Singh; Irfan Ansari (International Journal of Religious Tourism and Pilgrimage, 2023)
While religious sites are identified as unique experience spaces, offering diverse experiences, discourse on what constitutes a visitor’s experience still seems unsettled, primarily due to the fragmented approach owing to the classic binary of pilgrim-tourist. However, post-modern theories emphasise de-differentiation and blurring of boundaries between pilgrim-tourist and stress the need to add a new perspective to enhance the understanding of visitor experience at religious sites to manage tourism at such destinations efficiently. Therefore, the present study is undertaken to respond to this call and aims to identify constructs that shape visitors’ experience at religious sites. Building upon the synthesis of knowledge available in previous studies, the present review draws an integrated view of visitors’ experiences by combining the sacred-secular dichotomy. It offers a preliminary conceptual framework on constructs associated with visitors’ experiences by following the systematic and inductive methods. The study has identified four major constructs named- Destination Attributes, Visitor Attributes, Engagement, and Image, with fifteen sub-constructs, and suggests the location of visitor experience within the complex overlaps of these constructs.